Peran Strategi Pemasaran Digital Beauty Commerce terhadap Customer Satisfaction dan Repurchase Intention - Jaehan Fairuz Zahran; Usep Suhud; Ryna Parlyna (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the influence of Customer Engagement, Product Diversity, and Loyalty Program on Customer Satisfaction and their implications for Repurchase Intention among SOCO App by Sociolla users. This study employs a quantitative approach involving 250 respondents selected through purposive sampling. Data were collected through online questionnaires and analyzed using Structural Equation Modeling (SEM) with AMOS. The results indicate that Customer Engagement has a positive and significant effect on both Customer Satisfaction and Repurchase Intention. Product Diversity also has a positive and significant effect on Customer Satisfaction but does not significantly affect Repurchase Intention. Meanwhile, Loyalty Program and Customer Satisfaction are not proven to have significant effects on Repurchase Intention. These findings suggest that customer engagement is the most dominant factor in shaping satisfaction and repurchase intention, while product diversity plays a greater role in enhancing satisfaction without directly driving repurchase behavior. The loyalty program offered has not been effective as a determinant of satisfaction or repurchase intention in the beauty commerce context. This study contributes to beauty commerce platform managers in designing digital marketing strategies oriented toward customer engagement and product diversification.